Quantification of collateral artery growth by automated fluorescent microsphere perfusion - Meder, Benjamin; Just, Steffen; Katus, Hugo (International journal of cardiology, 2012)
Background: Since their introduction, genetically modified mice have become more and more important to examine molecular mechanisms involved in vascular growth. Today the gold standard for measuring vessel conductivity is to directly assess in vivo perfusion. However, this usually becomes more complicated the smaller the animal, especially due to the need for extensive instrumentation and requirement of maximal vasodilation. Methods: We developed an automated system that allows pressure-controlled in vivo perfusion of small animals with differently labeled fluorescent microspheres. Results: Besides precise operation of the system (mean pressures divergence 0.08%), automation of small animal microsphere perfusion is reliable and highly accurate in mice with and without femoral artery occlusion. In sham-operated control mice, which did not undergo femoral occlusion, highly reproducible measurements of hind limb perfusion (right vs. left=1.03±0.037) could be assessed. In mice after unilateral femoral artery occlusion, mean perfusion ratios of the automated method (ratio occluded vs. non-occluded hind limb=0.598±0.046) were comparable to the manual approach (0.561±0.062). However, inter-individual variances were significantly smaller with the automated system. Conclusion: We describe here a novel and innovative technical approach for pressure-controlled fluid handling specifically designed for microsphere perfusion measurements in small animals.